A Bible Scholar Looks at BAR’s Coverage of the Exodus - Radday, Yehuda T.; Radday, Yehuda T. (1982)
Recent issues of BAR have covered a wide range of views regarding the Israelites’ servitude in Egypt, the parting of the "Red Sea" (the "Reed Sea" in Hebrew), and the route of the Exodus.a The authors were, in the main, archaeologists, linguists and experts in Near Eastern studies. Perhaps it would be appropriate to […]